2019
DOI: 10.1016/j.rsma.2019.100683
|View full text |Cite
|
Sign up to set email alerts
|

Climate vulnerability, impacts and adaptation in Central and South America coastal areas

Abstract: Central and South America coasts are vulnerable to climate-related hazards.• Sea-level rise and vulnerability pose constraints to adaptation.• Climate Change puts demands on coastal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…In the RdlP estuary (Argentina-Uruguay), environmental variations are likely to modify plankton and fish distributions and abundances. The expected rainfall increase and southeastern winds and sea-level increase for 2050 will have contrasting effects as following: decreased/increased seawater intrusion/salinity and inward/seaward displacement of the EFS [ 38 , 39 ]. Together with the increased water temperature, they would affect the mixing-stratification cycle, primary productivity and oxygen levels in the estuarine front [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the RdlP estuary (Argentina-Uruguay), environmental variations are likely to modify plankton and fish distributions and abundances. The expected rainfall increase and southeastern winds and sea-level increase for 2050 will have contrasting effects as following: decreased/increased seawater intrusion/salinity and inward/seaward displacement of the EFS [ 38 , 39 ]. Together with the increased water temperature, they would affect the mixing-stratification cycle, primary productivity and oxygen levels in the estuarine front [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Implementing adaptation plans and effective measures in the RdlP Basin and estuary is complex due to its dimensions, dams and multi-country transboundary nature [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The promotion of information about climate to coastal inhabitants is therefore important to improve their preparedness against disasters regarding agricultural activities. It was found that early warning systems for climatic hazards in coastal areas save lives and agriculture, as well as improving adaptive capacity [152]. Information about climate change can be sent through several types of social networks in coastal communities, ensuring a greater exchange of climate change information [153].…”
Section: Micro-level: Farmer Perceptions Awareness and Educationmentioning
confidence: 99%